Tandem catalysis in electrocatalytic nitrate reduction: Unlocking efficiency and mechanism - Ziyang Wu; Yanhui Song; Haocheng Guo; Fengting Xie; Yuting Cong; Min Kuang; Jianping Yang (Interdisciplinary Materials, 2024)
Abstract The electrochemical nitrate reduction reaction (NO3RR) holds promise for ecofriendly nitrate removal. However, the challenge of achieving high selectivity and efficiency in electrocatalyst systems still significantly hampers the mechanism understanding and the large‐scale application. Tandem catalysts, comprising multiple catalytic components working synergistically, offer promising potential for improving the efficiency and selectivity of the NO3RR. This review highlights recent progress in designing tandem catalysts for electrochemical NO3RR, including the noble metal‐related system, transition metal electrocatalysts, and pulsed electrocatalysis strategies. Specifically, the optimization of active sites, interface engineering, synergistic effects between catalyst components, various in situ technologies, and theory simulations are discussed in detail. Challenges and opportunities in the development of tandem catalysts for scaling up electrochemical NO3RR are further discussed, such as stability, durability, and reaction mechanisms. By outlining possible solutions for future tandem catalyst design, this review aims to open avenues for efficient nitrate reduction and comprehensive insights into the mechanisms for energy sustainability and environmental safety.